2021
DOI: 10.1186/s12885-021-07952-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge towards cervical cancer screening and associated factors among urban health extension workers at Addis Ababa, Ethiopia: facility based cross-sectional survey

Abstract: Background Cervical cancer is preventable and remains a leading cause of avoidable death among women in the world. In a developing country, the knowledge of screening for cervical cancer behavior still very low. However, little is known about the knowledge towards cervical cancer screening of urban health extension workers in Ethiopia. This study aimed to assess knowledge towards cervical cancer screening and associated factors among urban health extension workers in Addis Ababa, Ethiopia, 2020… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…Those who had been screened for cervical cancer were more likely than those who had not. Regarding the practice of cervical cancer the study showed 18.4% participants screened for cervical cancer this is greater the previous studies done among women globally 13.26% [ 12 ], in Nepal and Tanzania 13.6% and 14.3% respectively [ 15 , 16 ], Ethiopia 2.9% [ 8 ] and study in Addis Ababa 3.5% [ 8 ]. The difference is due to time, location difference, availability of health facility and availability of screening service near to participant and knowledge of participants.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Those who had been screened for cervical cancer were more likely than those who had not. Regarding the practice of cervical cancer the study showed 18.4% participants screened for cervical cancer this is greater the previous studies done among women globally 13.26% [ 12 ], in Nepal and Tanzania 13.6% and 14.3% respectively [ 15 , 16 ], Ethiopia 2.9% [ 8 ] and study in Addis Ababa 3.5% [ 8 ]. The difference is due to time, location difference, availability of health facility and availability of screening service near to participant and knowledge of participants.…”
Section: Discussionmentioning
confidence: 65%
“…Further, in 2015 with in Addis Ababa, 27.7% women had adequate knowledge of cervical cancer screening [ 8 ]. On the other hand, on urban health extension workers studied, 48.4% had good knowledge about cervical cancer screening [ 12 ]. The difference may be due to access for health facilities and availability of technology, time gap of the study, and different in educational statue of participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection instruments used for this study consisted of the demographic survey and other forms to measure knowledge and awareness of HPV. The following forms were adapted to measure the knowledge and awareness of HPV: HPV Infection Awareness Questions [ 21 ], HPV Infection Knowledge Questions (Scale) [ 21 , 22 ], HPV Vaccine Knowledge Questions (Scale) [ 21 , 23 ] and Cervical Cancer Awareness on OC Pills [ 24 , 25 , 26 ]. The data instrument was adapted for use in the study settings.…”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopia, cervical cancer ranks as the second cause of cancer death, next to breast cancer, and is common among women aged 35–44 years old 11. More than 4648 women are diagnosed with cervical cancer each year, among them 3235 die annually 6.…”
Section: Introductionmentioning
confidence: 99%